An updated taxonomic treatment for Saxifraga callosa sensu amplo (Saxifragaceae) - Tavilla, Gianmarco; Guacchio, Emanuele Del (Phytotaxa, 2023)
Saxifraga callosa sensu amplo is a western Mediterranean orophilous taxon that is highly variable in morphology and whose populations tend toward isolation and diversification. According to the most followed treatment, it includes S. callosa subsp. callosa in SE France and Italy and subsp. catalaunica in Spain, often regarded as a distinct species. Within the autonym subspecies, two varieties are recognized by most authors, i.e., S. callosa var. callosa, occupying the northern part of the species range, and var. australis, occurring throughout the Apennines, in Sardinia and Sicily. Saxifraga lantoscana, described from SE France and reported for several localities also in NE Italy is a debated taxon, generally included in S. callosa subsp. callosa. In this contribution, we propose an updated taxonomic treatment that takes in account floristic, molecular, morphometric, and phytosociological data. According to this synthesis, S. catalaunica is a distinct species endemic to NE Spain, while S. callosa var. australis is re-evaluated at subspecific rank, with validation of the proper combination. Saxifraga lantoscana is recognized as the hybrid between S. callosa subsp. callosa and S. cochlearis. Finally, a full synonymy consistent with our proposal is provided.